Intermittent hypoxic training: Fact and fancy - Levine, B. (High Altitude Medicine & Biology, 2002)
Intermittent hypoxic training (IHT) refers to the discontinuous use of normobaric or hypobaric hypoxia, in an attempt to reproduce some of the key features of altitude acclimatization, with the ultimate goal to improve sea-level athletic performance. In general, IHT can be divided into two different strategies: (1) providing hypoxia at rest with the primary goal being to stimulate altitude acclimatization or (2) providing hypoxia during exercise, with the primary goal being to enhance the training stimulus. Each approach has many different possible application strategies, with the essential variable among them being the "dose" of hypoxia necessary to achieve the desired effect. One approach, called living high-training low, has been shown to improve sea-level endurance performance. This strategy combines altitude acclimatization (2500 m) with low altitude training to ensure high-quality training. The opposite strategy, living low-training high, has also been proposed by some investigators. The primacy of the altitude acclimatization effect in IHT is demonstrated by the following facts: (1) living high-training low clearly improves performance in athletes of all abilities, (2) the mechanism of this improvement is primarily an increase in erythropoietin, leading to increased red cell mass, VO2max, and running performance, and (3) rather than intensifying the training stimulus, training at altitude or under hypoxia leads to the opposite effect - reduced speeds, reduced power output, reduced oxygen flux - and therefore is not likely to provide any advantage for a well-trained athlete.